A proton exchange membrane for all-vanadium liquid flow battery and a preparation method thereof
By blending bismuth catalyst, phosphine coordination compound and N,N'-carbonyl diimidazole in the proton exchange membrane of all vanadium flow battery, the existing membrane voltage efficiency and low Coulomb efficiency are solved, and the battery energy efficiency is improved.
Patent Information
- Application Number
- CN202411535110.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-10-31
AI Technical Summary
The existing perfluorosulfonic acid proton exchange membranes have problems with low voltage efficiency and Coulomb efficiency in all vanadium flow batteries, mainly due to large membrane internal resistance and low efficiency of vanadium ions passing through the membrane.
By blending bismuth catalyst, phosphine coordination compound and N,N'-carbonyldiimidazole into the perfluorosulfonic acid membrane solution, the action of the proton membrane and bismuth ions are enhanced, and the anionic group in the ligand attracts vanadium ions to the surface, thereby improving the catalytic effect.
It improves the voltage efficiency and Coulomb efficiency of the battery, reduces the activation overpotential of the chemical conversion of electroactive substances, and improves energy efficiency.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of liquid flow battery energy storage, and in particular relates to a proton exchange membrane for an all-vanadium liquid flow battery and a preparation method thereof. Background Art
[0002] With the efficient use of renewable energy such as wind and solar energy, the demand for large and medium-sized energy storage is increasing. All-vanadium redox flow batteries (VRFB) have attracted much attention due to their advantages such as fast response to changes in energy demand, small impact on the environment, long life cycle, and flexible operation. Compared with other flow batteries, VRFB uses VO 2+ / VO2 and V 3+ / V 2+ The redox pair serves as the positive and negative electrolytes, avoiding cross-contamination of the positive and negative electrolyte active substances during the long-term operation of the battery system, thus significantly reducing costs.
[0003] The proton exchange membrane is a key component of VRFB, which determines the efficiency, life and cost of the VRFB system. The membrane is used to separate the positive and negative half-cells and provide proton conduction function. The ideal VRFB membrane should have high proton conductivity and excellent stability. The current technical direction of the mainstream perfluorosulfonic acid proton exchange membrane is to balance the optimal values of coulombic efficiency and voltage efficiency. When the membrane thickness is large, the internal resistance of the membrane becomes larger, and the voltage efficiency of the battery is low. When the membrane thickness is low, vanadium ions are more likely to pass through the membrane, thereby reducing the coulombic efficiency. This technical direction greatly limits the performance of the membrane itself and limits its use in all-vanadium liquid flow batteries.
[0004] Adding a catalyst to the system can reduce the electrochemical overpotential. CN106972186A mentions that a catalyst such as BiCl3 / Bi(NO3)3 can be coated on the surface of the proton exchange membrane to reduce the electrochemical overpotential. 3+ / V 2+ However, the BiCl3 / Bi(NO3)3 catalyst is easily soluble in the electrolyte and has a weak interaction with the proton exchange membrane, so it cannot fully play a catalytic role. Summary of the invention
[0005] In view of the problems in the prior art that the BiCl3 / Bi(NO3)3 catalyst is easily soluble in the electrolyte, has a weak interaction with the proton exchange membrane, and cannot fully exert its catalytic effect, the present invention provides a proton exchange membrane for an all-vanadium liquid flow battery and a preparation method thereof. The present invention blends a bismuth catalyst, a ligand, and N,N'-carbonyldiimidazole into a perfluorosulfonic acid membrane solution, and the coordination of the phosphine coordination compound can enhance the interaction between the proton membrane and the bismuth ion, and a large number of anionic groups in the ligand are also conducive to attracting vanadium ions to the surface, producing a better catalytic effect, and further improving the voltage efficiency of the battery; N,N'-carbonyldiimidazole can activate the sulfonic acid group, and the two substances cooperate synergistically, thereby reducing the activation overpotential of the chemical conversion of the electroactive substance, thereby improving the voltage efficiency and coulomb efficiency of the battery, and achieving the purpose of improving energy efficiency.
[0006] Specifically, the first aspect of the present invention provides a method for preparing a proton exchange membrane for an all-vanadium liquid flow battery, the method comprising the following steps:
[0007] (1) mixing a perfluorosulfonic acid resin solution, a bismuth salt catalyst, a phosphine coordination compound and N,N'-carbonyldiimidazole to obtain a membrane-forming solution;
[0008] (2) applying the film-forming solution obtained in step (1) on a substrate to obtain a wet film attached to the substrate;
[0009] (3) Drying and annealing the substrate and the wet film thereon, and peeling off the formed film from the substrate to obtain the proton exchange membrane for the all-vanadium redox flow battery.
[0010] In one or more embodiments, in the perfluorosulfonic acid resin solution, the mass fraction of the perfluorosulfonic acid resin is 5%-30%, preferably 10%-20%.
[0011] In one or more embodiments, in the perfluorosulfonic acid resin solution, the solvent is N,N-dimethylformamide.
[0012] In one or more embodiments, a perfluorosulfonic acid resin is dissolved in N,N-dimethylformamide to form the perfluorosulfonic acid resin solution.
[0013] In one or more embodiments, the bismuth salt catalyst is selected from one or more of bismuth chloride, bismuth nitrate, bismuth sulfate, and bismuth citrate.
[0014] In one or more embodiments, the phosphine coordination compound is a phosphine coordination compound containing a hydroxyl group, preferably one or more selected from hydroxyethylidene diphosphonic acid, bishydroxyethylphosphonic acid and hydroxyethylphosphonic acid.
[0015] In one or more embodiments, the mass ratio of the perfluorosulfonic acid resin to the bismuth salt catalyst is 1:(0.01-0.05).
[0016] In one or more embodiments, the mass ratio of the bismuth salt catalyst to the phosphine coordination compound is 1:(0.01-0.06).
[0017] In one or more embodiments, the molar ratio of the phosphine coordination compound to N,N'-carbonyldiimidazole is 1:(0.8-1.2).
[0018] In one or more embodiments, the material of the substrate layer is selected from one or more of PEN, PI and PET.
[0019] In one or more embodiments, the coating is performed by solution casting.
[0020] In one or more embodiments, the coating speed is 8-15 mm / s.
[0021] In one or more embodiments, the drying method is oven drying, the oven drying temperature is preferably 120-160° C., and the oven drying time is preferably 8-12 min.
[0022] In one or more embodiments, the annealing temperature is 180-220° C., and the annealing time is 18-22 min.
[0023] In one or more embodiments, the proton exchange membrane for all-vanadium redox flow battery has a thickness of 30-50 μm.
[0024] A second aspect of the present invention provides a proton exchange membrane for an all-vanadium redox flow battery, which is prepared by the method for preparing a proton exchange membrane for an all-vanadium redox flow battery as described in any embodiment of the present invention.
[0025] A third aspect of the present invention provides an all-vanadium liquid flow battery, which includes a proton exchange membrane for an all-vanadium liquid flow battery as described in any embodiment of the present invention.
[0026] A fourth aspect of the present invention provides the use of a proton exchange membrane for an all-vanadium redox flow battery as described in any embodiment herein in improving the energy efficiency of the all-vanadium redox flow battery.
[0027] A fifth aspect of the present invention provides the use of a phosphine coordination compound and N,N'-carbonyldiimidazole in the preparation of a proton exchange membrane for an all-vanadium redox flow battery.
[0028] The sixth aspect of the present invention provides the use of phosphine coordination compounds and N,N'-carbonyldiimidazole in reducing the dissolution of bismuth salt catalysts in proton exchange membranes for all-vanadium redox flow batteries into electrolytes and increasing the interaction between bismuth salt catalysts and proton exchange membranes. DETAILED DESCRIPTION
[0029] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in this article. Unless otherwise specified, all technical and scientific terms used in this article are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definitions in this article shall prevail.
[0030] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0031] Herein, “comprising”, “including”, “containing” and similar terms encompass the meanings of “consisting essentially of” and “consisting of”. For example, when “A comprises B and C” is disclosed herein, “A consists essentially of B and C” and “A consists of B and C” should be deemed to be disclosed herein.
[0032] In this document, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible sub-ranges and individual values within the range (including integers and fractions).
[0033] In this document, unless otherwise specified, percentage refers to mass percentage and ratio refers to mass ratio.
[0034] Herein, when describing embodiments or examples, it should be understood that they are not used to limit the present invention to these embodiments or examples. On the contrary, all substitutes, improvements and equivalents of the methods and materials described in the present invention can be included in the scope limited by the claims.
[0035] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0036] The present invention provides a method for preparing a proton exchange membrane for an all-vanadium liquid flow battery, the method comprising the following steps:
[0037] (1) mixing a perfluorosulfonic acid resin solution, a bismuth salt catalyst, a phosphine coordination compound and N,N'-carbonyldiimidazole to obtain a membrane-forming solution;
[0038] (2) applying the film-forming solution obtained in step (1) on a substrate to obtain a wet film attached to the substrate;
[0039] (3) Drying and annealing the substrate and the wet film thereon, and peeling off the formed film from the substrate to obtain the proton exchange membrane for the all-vanadium redox flow battery.
[0040] In the perfluorosulfonic acid resin solution of the present invention, the mass fraction of the perfluorosulfonic acid resin may be 5%-30%, preferably 10%-20%. In some embodiments, the solvent is N,N-dimethylformamide.
[0041] In some embodiments, the perfluorosulfonic acid resin is dissolved in a solvent such as N,N-dimethylformamide to form a perfluorosulfonic acid resin solution. In some specific embodiments, the perfluorosulfonic acid resin is dissolved in N,N-dimethylformamide and stirred until completely dissolved. The dissolving temperature may be 20-80°C or 60°C-80°C. An exemplary stirring time may be 3-5h.
[0042] In some embodiments, the perfluorosulfonic acid resin dispersion is evaporated to obtain a dried perfluorosulfonic acid resin. Commercially available perfluorosulfonic acid resin dispersions, such as Nafion D520 dispersions and Nafion D2020 dispersions, can be used. The temperature and time for evaporating the perfluorosulfonic acid resin dispersion can be determined according to the properties of the resin dispersion itself, such as the type of solvent, to obtain the perfluorosulfonic acid resin. The evaporation temperature can be 60-120° C. or 70-90° C. The evaporation time can be 8-12 hours.
[0043] In the present invention, the bismuth salt catalyst is selected from one or more of bismuth chloride, bismuth nitrate, bismuth sulfate and bismuth citrate. The mass ratio of the perfluorosulfonic acid resin to the bismuth salt catalyst can be 1:(0.01-0.05), such as 1:(0.03-0.05).
[0044] In the present invention, the phosphine coordination compound is selected from one or more of hydroxyethylidene diphosphonic acid, bis(hydroxyethyl)phosphonic acid and hydroxyethylphosphonic acid. The mass ratio of the bismuth salt catalyst to the phosphine coordination compound can be 1:(0.01-0.06), such as 1:(0.04-0.06). The inventors have found through experiments that among many ligands, the effect of selecting phosphine coordination compounds and bismuth ions is better, and the coordination effect can enhance the effect of proton membrane and bismuth ions, and the large number of anionic groups in the ligands are also conducive to attracting vanadium ions to the surface, resulting in better catalytic effect and further improving the voltage efficiency of the battery. In addition, the inventors have further found that selecting a phosphine coordination compound containing a hydroxyl group can facilitate the reaction of the ligand with the sulfonate.
[0045] In the present invention, the molar ratio of the phosphine coordination compound to N,N'-carbonyldiimidazole can be 1:(0.8-1.2), such as 1:0.9, 1:1, 1:1.1 or any range of the above two ratios. N,N'-carbonyldiimidazole can activate the sulfonic acid group and further promote its reaction with the hydroxyl group.
[0046] In step (1), a perfluorosulfonic acid resin solution, a bismuth salt catalyst, a phosphine coordination compound and N,N'-carbonyldiimidazole are mixed and then dispersed to obtain a film-forming solution. The dispersion method can be dispersed using a homogenizer. There is no particular limitation on the dispersion time and speed, as long as the dispersion is uniform. An exemplary dispersion time can be 10 min-30 min, and the dispersion speed can be 10000-20000 rpm.
[0047] The material of the substrate suitable for the present invention can be selected from one or more of PEN (polyethylene naphthalate), PI (polyimide) and PET (ethylene terephthalate).
[0048] In some embodiments, in step (2), the film-forming liquid can be poured onto the substrate and coated by a casting coater. The coating gap can be 350-450 μm, such as 400-420 μm. The coating speed can be 8-15 mm / s, such as 9-12 mm / s. The coating thickness of the film-forming liquid on the substrate surface can be adjusted according to the target thickness of the film.
[0049] In some embodiments, in step (3), the obtained wet film can be placed in an oven such as a forced air oven for drying to evaporate the solvent. The drying temperature can be 120-160° C., such as 135-145° C. The drying time can be 8-12 min.
[0050] After drying, a dry film is obtained, and then annealing is performed. In some embodiments, the dry film can be placed in an oven such as a forced air oven for annealing. The annealing conditions can be an annealing temperature of 180-220° C. and an annealing time of 18-22 minutes. The membrane is peeled off from the substrate to obtain the final proton exchange membrane.
[0051] The present invention also includes an all-vanadium redox flow battery, which comprises a positive electrode, a negative electrode, a proton exchange membrane of the present invention and an electrolyte. The positive and negative electrodes of the battery are separated by the proton exchange membrane of the present invention.
[0052] In the present invention, the structure of the all-vanadium redox flow battery, the positive and negative electrolytes, and the method for making the all-vanadium redox flow battery are conventional in the art. The positive electrolyte and the negative electrolyte can be vanadium ion solutions of different valence states. For example, the positive electrolyte can be VOSO4 + A solution of sulfuric acid, wherein the concentration of VOSO4 is 1.6-1.8 mol / L, such as 1.7±0.05 mol / L, and the concentration of sulfuric acid is 2-4 mol / L. The negative electrode electrolyte can be VSO4 + A solution of sulfuric acid, wherein the concentration of VSO4 can be 1.4-1.6 mol / L such as 1.5±0.05 mol / L, and the concentration of sulfuric acid can be 2-4 mol / L.
[0053] Beneficial effects of the present invention:
[0054] The present invention prepares a proton exchange membrane for an all-vanadium redox flow battery by mixing a bismuth salt catalyst, a phosphine coordination compound, and N,N'-carbonyldiimidazole into a perfluorosulfonic acid resin solution, which can reduce the activation overpotential of the chemical conversion of the electroactive substance, thereby improving the voltage efficiency and coulomb efficiency of the battery, thereby achieving the purpose of improving energy efficiency. The preparation method of the present invention has a simple process, excellent electrochemical performance, low cost, and is easy to mass produce.
[0055] The present invention will be described below in the form of specific examples. It should be understood that these examples are merely illustrative and are not intended to limit the scope of the present invention. The methods, reagents and materials used in the examples are, unless otherwise stated, conventional methods, reagents and materials in the art. The raw material compounds in the examples can all be purchased through commercial routes.
[0056] The Nafion D520 resin dispersion used in the examples and comparative examples was purchased from Thermo Fisher Scientific.
[0057] Example 1
[0058] Step (1): First, pour the purchased Nafion 520 dispersion into an evaporating dish, adjust the oven to 80°C, and place the evaporating dish in the oven for 10 hours to obtain Nafion resin. Add 20g of the obtained Nafion resin and 80g of DMF solvent into a reactor, stir at 80°C for 4 hours, and set the stirring speed to 300 rpm. Stop stirring after observing that the Nafion resin is completely dissolved, and obtain a perfluorosulfonic acid resin solution with a mass fraction of 20wt%.
[0059] Take 100 g of the prepared perfluorosulfonic acid resin solution, add 0.62 g of bismuth chloride solid, 0.031 g of hydroxyethylidene diphosphonic acid solid, and 0.024 g of N,N'-carbonyldiimidazole into the solution, and disperse it with a homogenizer at 15000 rpm for 30 minutes to obtain a film-making solution.
[0060] Step (2): Pour the film-making solution obtained in the previous step onto the PEN substrate, set the gap of the casting coater to 400 μm, and set the running speed to 10 mm / s to obtain a wet film attached to the substrate.
[0061] Step (3): Place the wet film obtained in the previous step in a 140°C forced air oven and remove the solvent for 10 minutes to obtain a dry film; then place the dry film in a 200°C forced air oven and anneal for 20 minutes, peel off the film from the substrate, and obtain a 40 μm thick proton exchange membrane for all-vanadium liquid flow battery.
[0062] Example 2
[0063] The difference between Example 2 and Example 1 is that in step (1), the amount of bismuth chloride solid added in Example 1 is 1 g; the amount of hydroxyethylidene diphosphonic acid solid added is 0.05 g. In step (2), the gap of the applicator is 410 μm. The remaining operating conditions and steps are the same as those in Example 1.
[0064] Example 3
[0065] The difference between Example 3 and Example 1 is that the bismuth chloride solid in Example 1 is replaced with bismuth nitrate solid. The remaining operating conditions and steps are the same as those in Example 1.
[0066] Example 4
[0067] The only difference between Example 4 and Example 1 is that the hydroxyethylidene diphosphonic acid solid in Example 1 is replaced with bis(hydroxyethyl)phosphonic acid solid. The remaining operating conditions and steps are the same as those in Example 1.
[0068] Comparative Example 1
[0069] Step (1): First, pour the purchased Nafion 520 dispersion into an evaporating dish, adjust the oven to 80°C, and place the evaporating dish in the oven for 10 hours to obtain Nafion resin. Add 20g of the obtained Nafion resin and 80g of DMF solvent into a reactor, stir at 80°C for 4 hours, and set the stirring speed to 300 rpm. Stop stirring after observing that the Nafion resin is completely dissolved, and obtain a perfluorosulfonic acid resin solution with a mass fraction of 20wt%.
[0070] 100 g of the prepared perfluorosulfonic acid resin solution was taken, and 0.62 g of bismuth chloride solid was added to the solution. The mixture was dispersed evenly by a homogenizer at 15,000 rpm for 30 minutes to obtain a membrane-making solution.
[0071] Step (2): Pour the film-making solution obtained in the previous step onto the PEN substrate, set the gap of the casting coater to 400 μm, and set the running speed to 10 mm / s to obtain a wet film attached to the substrate.
[0072] Step (3): Place the wet membrane obtained in the previous step in a 140°C forced air oven and remove the solvent for 10 minutes to obtain a dry membrane; then place the dry membrane in a 200°C forced air oven and anneal for 20 minutes to obtain a 40 μm thick proton exchange membrane for all-vanadium liquid flow battery.
[0073] Comparative Example 2
[0074] The only difference between Comparative Example 2 and Example 1 is that no hydroxyethylidene diphosphonic acid solid is added.
[0075] Comparative Example 3
[0076] The only difference between Comparative Example 3 and Example 1 is that N,N'-carbonyldiimidazole is not added.
[0077] Test Example 1
[0078] The battery preparation conditions are: the active substances in the positive and negative electrolytes are 1.7 mol / LV 4+ / V 5+ and 1.5 mol / LV 2+ / V 3+ The supporting electrolyte is 3 mol / L sulfuric acid, the volume of the positive and negative electrolytes is 70 mL, the electrode is a carbon felt electrode, and the effective area of the carbon felt electrode is 48 cm 2 , the compression ratio is 40%.
[0079] The performance of the all-vanadium redox flow battery prepared by using the proton exchange membrane for all-vanadium redox flow battery of Examples 1-4 and Comparative Examples 1-3 was tested. The test conditions were as follows: at a current density of 80 mA / cm 2 -200mA / cm 2The charge and discharge experiments were carried out under the following conditions: charging to 1.55V, discharging to 1.00V, and the battery operating temperature was 30°C.
[0080] The coulombic efficiency, voltage efficiency and energy efficiency results of the all-vanadium liquid flow batteries prepared using the proton exchange membranes of Examples 1-4 and Comparative Examples 1-3 are shown in Table 1.
[0081] Table 1: Performance test of proton membrane vanadium redox flow battery at different current densities
[0082]
[0083] As can be seen from the table, compared with comparative examples 1-3, examples 1-4 have higher efficiency performance. This is because the phosphonic acid group in the ligand and N,N'-carbonyldiimidazole are used in combination to better retain the bismuth element in the catalyst, allowing it to better exert its catalytic performance, improve the voltage efficiency of the battery, and achieve the purpose of improving energy efficiency.
[0084] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.
Claims
1. A method for preparing a proton exchange membrane for an all-vanadium liquid flow battery, characterized in that: The method comprises the following steps: (1) mixing a perfluorosulfonic acid resin solution, a bismuth salt catalyst, a phosphine coordination compound and N,N'-carbonyldiimidazole to obtain a membrane-forming solution; wherein the mass fraction of the perfluorosulfonic acid resin in the perfluorosulfonic acid resin solution is 5%-30%; and the phosphine coordination compound is a phosphine coordination compound containing a hydroxyl group; (2) applying the film-forming solution obtained in step (1) on a substrate to obtain a wet film attached to the substrate; (3) Drying and annealing the substrate and the wet film thereon, and peeling off the formed film from the substrate to obtain the proton exchange membrane for the all-vanadium redox flow battery.
2. The method for preparing a proton exchange membrane for an all-vanadium redox flow battery according to claim 1, characterized in that: In the perfluorosulfonic acid resin solution, the mass fraction of the perfluorosulfonic acid resin is 10%-20%; and / or In the perfluorosulfonic acid resin solution, the solvent is N,N-dimethylformamide.
3. The method for preparing a proton exchange membrane for an all-vanadium redox flow battery according to claim 1, characterized in that: The bismuth salt catalyst is selected from one or more of bismuth chloride, bismuth nitrate, bismuth sulfate and bismuth citrate; and / or The phosphine coordination compound is selected from one or more of hydroxyethylidene diphosphonic acid, bishydroxyethylphosphonic acid and hydroxyethylphosphonic acid.
4. The method for preparing a proton exchange membrane for an all-vanadium redox flow battery according to claim 1, characterized in that: The mass ratio of the perfluorosulfonic acid resin to the bismuth salt catalyst is 1:(0.01-0.05); and / or The mass ratio of the bismuth salt catalyst to the phosphine coordination compound is 1:(0.01-0.06); and / or The molar ratio of the phosphine coordination compound to N,N'-carbonyldiimidazole is 1:(0.8-1.2).
5. The method for preparing a proton exchange membrane for an all-vanadium redox flow battery according to claim 1, characterized in that: The material of the substrate layer is selected from one or more of PEN, PI and PET; and / or The coating method is solution casting coating; the coating speed is 8-15 mm / s.
6. The method for preparing a proton exchange membrane for an all-vanadium redox flow battery according to claim 1, characterized in that: The drying method is drying, the drying temperature is 120-160° C., and the drying time is 8-12 minutes; and / or The annealing temperature is 180-220° C., and the annealing time is 18-22 minutes.
7. The method for preparing a proton exchange membrane for an all-vanadium redox flow battery according to claim 1, characterized in that: The thickness of the proton exchange membrane for the all-vanadium liquid flow battery is 30-50 μm.
8. A proton exchange membrane for an all-vanadium liquid flow battery, characterized in that: The membrane is prepared by the method for preparing a proton exchange membrane for an all-vanadium liquid flow battery as described in any one of claims 1 to 7.
9. An all-vanadium liquid flow battery, characterized in that: It comprises the proton exchange membrane for all-vanadium liquid flow battery as claimed in claim 8.
10. Use of the proton exchange membrane for all-vanadium redox flow battery as claimed in claim 8 in improving the energy efficiency of all-vanadium redox flow battery.
Citation Information
Patent Citations
Preparation method of composite membrane with catalytic function for positive and negative electrodes used for all-vanadium redox flow batteries
CN106972186A
Cross-linking perfluorinated sulfonic acid ion exchange membrane and preparation method thereof
CN101764233A
Preparation method of high-performance composite proton exchange membrane of fuel cell
CN102623734A